PREPARATION OF MESO POROUS SILICA FROM BENTONITE BY ULTRAFINE GRINDING AND SELECTIVE LEACHING - Agus wahyudi; SARIMAN SARIMAN; SITI ROCHANI (Puslitbang tekMIRA, 2010)
Preparation of meso porous silica from bentonite had been conducted by ultrafine grinding and leaching. The bentonite was taken from Nanggung, Bogor, West Java; it contains montmorillonite with porous struc- ture. The ultrafine grinding was carried out using planetary ball mill (PBM) in wet condition (wet milling) in methanol. Optimum milling time was reached in 30 hours and it produced 77.4 nm of particle size. The process was continued with selective leaching in sulphuric acid solution to increase the amount of SiO2 from 54.13% to 86.21%, which decreased Al2O3 and Fe2O3 content gradually from 23.09% and 7.33% to 4.96% and 0.89% respectively. The leaching process produced porous silica material with pore size 6.5 nm (meso porous); 278 m2/g of surface area and 0.75 mL/g of pore volume.